Peran Pendidikan Agama dalam Membentuk Perilaku Moral AUD: Studi Literatur - Leksa Cantika Weti; Fitri Febri Handayani; Naili Rohmah (Early Childhood Research Journal (ECRJ), 2026)
This study aims to investigate the contribution of religious education to the formation of moral behavior in early childhood by systematically analyzing the literature. The method applied is descriptive qualitative, by reviewing various relevant sources in the period 2020 to 2025. The research findings indicate that religious education plays a significant role in instilling fundamental moral values such as honesty, responsibility, empathy, and discipline from an early age. These values are the basis for the formation of children's character. The effectiveness of religious education is largely determined by the teaching methods applied, where an interactive approach that is in accordance with the child's developmental phase is more easily accepted and understood. In addition, collaboration between formal education in schools with the family and community environment determines the success of internalizing religious teachings. Challenges found in the implementation of religious education for early childhood include lack of training for teachers, low parental participation, and the impact of digital media. Therefore, religious education needs to be delivered holistically and relevantly, not only in the form of teaching teachings, but also through habits and real practices in everyday life. This study emphasizes the importance of a comprehensive approach in implementing religious education to form ethical and strong individuals from a young age.